Imaging Update on the Glenoid Labrum: Variants versus Tears - Gustas, Cristy N.; Tuite, Michael J. (Seminars in Musculoskeletal Radiology, 2014)
This article reviews the normal labral variants of the shoulder and describes imaging features, including secondary signs, to help discriminate tears from normal variants. The labral variants can be divided into two main groups. One group is composed of nonstandard appearances in the labral shape, signal intensity, or the site of affixation to the glenoid rim. The other group consists of classic labral variants, where the labrum is partially or completely unattached to the subjacent bone, or a segment of the labrum is absent.
Keywords: labrum; variant; sublabral recess; sublabral foramen; Buford complex